Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
6 - 1 × 0 + 2 ÷ 2
Following the order of simplification, we first have to divide, then multiply, then add and then subtract.
= 6 - 1 × 0 + 1
= 6 - 0 + 1
= 6 + 1
= 7
So, the answer is 7
Following the order of simplification, we first have to divide, then multiply, then add and then subtract.
= 6 - 1 × 0 + 1
= 6 - 0 + 1
= 6 + 1
= 7
So, the answer is 7
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.